2012
DOI: 10.1145/2366145.2366183
|View full text |Cite
|
Sign up to set email alerts
|

Foveated 3D graphics

Abstract: We exploit the falloff of acuity in the visual periphery to accelerate graphics computation by a factor of 5-6 on a desktop HD display (1920×1080). Our method tracks the user's gaze point and renders three image layers around it at progressively higher angular size but lower sampling rate. The three layers are then magnified to display resolution and smoothly composited. We develop a general and efficient antialiasing algorithm easily retrofitted into existing graphics code to minimize "twinkling" artifacts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
216
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(223 citation statements)
references
References 33 publications
(38 reference statements)
3
216
0
4
Order By: Relevance
“…Vlachos [17] presented a stencil mesh to cull hidden areas after warping in advance. Foveated rendering [18] is a gaze-contingent multi-resolution rendering technique. By using eye trackers, this technique lowers image quality in the periphery (outside the fovea) to increase rendering performance.…”
Section: Vr Acceleration Techniquesmentioning
confidence: 99%
“…Vlachos [17] presented a stencil mesh to cull hidden areas after warping in advance. Foveated rendering [18] is a gaze-contingent multi-resolution rendering technique. By using eye trackers, this technique lowers image quality in the periphery (outside the fovea) to increase rendering performance.…”
Section: Vr Acceleration Techniquesmentioning
confidence: 99%
“…Guenter et al [10] introduced a foveated rendering approach, generating and blending together three images of different quality in real-time depending on the inputs from a desktop eye tracker. Instead of using the eye gaze for rendering optimizations, we introduce a foveated compression method to lower the required data rate for in-home streaming.…”
Section: Related Workmentioning
confidence: 99%
“…McConkie and Loschky [2002] have shown that a switch from a significant blur to a sharp image can be detected by the observer even 5 ms after the end of a saccade. However, the tolerable delay can grow to up to 60 ms [Loschky and Wolverton 2007] for more subtle blur changes as in multi-resolution techniques [Guenter et al 2012;Geisler and Perry 1998]. …”
Section: Saccadic Suppressionmentioning
confidence: 99%
“…In foveated rendering [Guenter et al 2012], the efficiency of image generation can be improved by maintaining high image resolution only around the gaze location. The authors reported that seamless rendering can be achieved with a latency below 40 ms.…”
Section: Other Gaze-driven Applicationsmentioning
confidence: 99%
See 1 more Smart Citation